Testing Techniques Selection: A Systematic Mapping Study - Santos, Italo; Melo, Silvana M.; de Souza, Paulo Sergio Lopes; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
[Context] Software projects must consider the selection of testing techniques and criteria during their life cycles. This practice increases the chances of testing activity to be appropriately performed. In a previous work, an infrastructure to support the selection of testing techniques was proposed for the context of concurrent software. This infrastructure considers information (attributes) of the project to make the selection closer to the testers need. [Objective] This paper extends the previous work by identifying new studies concerning testing techniques selection, project attributes that can be used for this selection and which approaches can be employed to support the combined selection. [Method] A mapping study was conducted and a total of 15 primary studies, published in the last 20 years were selected. Information about approaches to testing techniques selection was analyzed and classified. [Results] The following results were obtained: (i) existing approaches for selection of testing techniques; (ii) proposition of a taxonomy of selection approaches; (iii) characterization of attributes to offer the support for the selection of a testing technique; and (iv) identification of approaches that perform combined selection of testing techniques. [Conclusion] Combining testing techniques is essential to improve the testing activity quality by finding different failure categories and supplementing other techniques limitations. This paper describes an initiative to offer support for the construction of new or combined strategies for the selection of testing techniques capable of being used in practice.